Insecurity Dalam Lirik Lagu - Pramesetya, Sandra Astri; Sumardjijati, Sumardjijati (Universitas Garut, 2024)
Songs are one part of mass communication that utilizes language as a medium for conveying messages and aims to influence listeners. Through the song